A influência do coping religioso-espiritual na qualidade de vida de pais e mães, após a perda de um(a) filho(a) por causas externas - Parente, Natasha Torlay (2017)
This study sought to verify the influence of spiritual/religious coping (SRC) on the quality of life of a father and/or mother who has lost a child by external causes. It is a cross-sectional, quantitative and qualitative study. Participants were invited to collaborate voluntarily and after agreeing, they answered the questionnaires Spiritual Religious Coping Scale Brief (SRCOPE brief Scale), WHOQOL Spirituality Religiousness and Personal Beliefs, and the Duke Religious Index, DUREL. The population was composed by forty participants, constituted equally by twenty mothers and twenty fathers, who lost the child by external causes, with more than three months of time of the loss. The cause of death by homicide, represents 67.5%, traffic accident composes 15%, tragedy of Kiss Nightclub constitutes 12.5%, suicide evidences 2.45%, as well as and 2.45% for lost bullet. Fathers and mothers present high frequency of IR, as well as RO and RNO. Fathers and mothers aged 29 to 44 years have a higher religiosity than those aged over 44 years. Fathers manifest a higher Positive SRC (PSRC) Offer of Help (p = 0.0001), Positive attitude towards God (p = 0.0005) and lower Negative SRC (NSRC) (p = 0.007) than mothers. No correlation was found between quality of life, religious frequency and SRC. The qualitative results revealed that mothers have greater difficulty in dealing with loss, according to Stroebe and Shut (1999; 2001), Rando (1997), Schatz (1997); There was a marked presence of illusions related to the departed child, considered expressions of continuous bonds. The positive SRC (PSRC) was highlighted in the narrative of fathers and mothers, used as a resource to serve others, through volunteering and/or building prosocial institutions, to be beneficial for well-being as well as in the construction of meaning and in the search for purpose in life